2020
DOI: 10.1104/pp.19.01292
|View full text |Cite
|
Sign up to set email alerts
|

The BIR2/BIR3-Associated Phospholipase Dγ1 Negatively Regulates Plant Immunity

Abstract: A phospholipase D is a negative regulator of plant immunity and forms complexes with regulatory receptor-like kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 94 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, recent studies demonstrated that there is a reduction in PI4P and a specific enrichment of PI(4,5)P2 on interfacial membranes during successful infections, like the extra-haustorial membrane (EHM) in Arabidopsis powdery mildew infections, the extra-invasive hyphal membrane (EIHM) in Arabidopsis Colletotrichum infections or at the potato (solanum tuberosum) Phytophthora infestans infection sites [50][51][52] . The PI(4,5)P2 enrichment at the EHM and EIHM is an essential susceptibility factor, which is most likely pathogen-induced and requires the function of the host phosphatidylinositol 4- Likewise, a correlation between the lipid composition of the PM and immunity, as well as NLR (CNL) function and stability and an important function for phospholipase-dependent signalling in immunity was previously reported [55][56][57][58][59] . Plant phospholipase families C (PLCs) and D (PLDs) are involved in many aspects of abiotic and biotic stress responses 60 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, recent studies demonstrated that there is a reduction in PI4P and a specific enrichment of PI(4,5)P2 on interfacial membranes during successful infections, like the extra-haustorial membrane (EHM) in Arabidopsis powdery mildew infections, the extra-invasive hyphal membrane (EIHM) in Arabidopsis Colletotrichum infections or at the potato (solanum tuberosum) Phytophthora infestans infection sites [50][51][52] . The PI(4,5)P2 enrichment at the EHM and EIHM is an essential susceptibility factor, which is most likely pathogen-induced and requires the function of the host phosphatidylinositol 4- Likewise, a correlation between the lipid composition of the PM and immunity, as well as NLR (CNL) function and stability and an important function for phospholipase-dependent signalling in immunity was previously reported [55][56][57][58][59] . Plant phospholipase families C (PLCs) and D (PLDs) are involved in many aspects of abiotic and biotic stress responses 60 .…”
Section: Discussionmentioning
confidence: 87%
“…However, the exact mechanisms of how these enzymes and their product(s) influence immunity are not well understood 61 . Perception of pathogen-derived danger signals by NLRs and cell-surface localized pathogen-recognition receptors (PRRs) lead to rapid recruitment and specific activation of PLDs and PLCs and to their recruitment to pathogen entry sites at the PM, as well as a biphasic transient Ca 2+ influx 56,57,62 . PLDs and PLCs induce the production of inositol polyphosphates, phosphatidic acid (PA) and diacylglycerol (DAG), all of which can function as second messengers during immunity as well as other stress responses 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the regulation of PLDα1 in internalization of pathogen effectors via CME deserves more attention. PLDγ1 negatively regulates plant defense responses to bacteria and fungi by interacting with the BAK1-INTERACTING RECEPTOR-LIKE KINASES (BIR) BIR2 and BIR3; these proteins constitutively bind the co-receptor BAK1, preventing it from forming a receptor-ligand complex, thereby inhibiting receptor activation [68][69][70] (Figure 4B). BAK1 is released from the BIR2/3 complex upon ligand binding to the corresponding immune receptor [68,69].…”
Section: Phospholipid-based Signaling Integrates With Trafficking Pathways For Plant Immunitymentioning
confidence: 99%
“…pathway [70], we propose that microdomains function as sorting platforms for the regulation of PLD isoforms in immune responses through exocytosis or endocytosis. Alternatively, PLDgenerated PA can regulate exo-endocytic trafficking required for plant defense, because there is evidence that PA directly modifies membrane curvature or recruits important regulatory proteins involved in exocytosis, endocytosis, membrane fusion, and vesicle budding [2] (Figure 2).…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation